Dental and skeletal components of Class II open bite treatment with a modified Thurow appliance - Jacob, Helder Baldi (2014)
INTRODUCTION:Due to the lack of studies that distinguish between dentoalveolar and basal changes caused by the Thurow appliance, this clinical study, carried out by the School of Dentistry - State University of São Paulo/Araraquara, aimed at assessing the dental and skeletal changes induced by modified Thurow appliance.METHODS:The sample included an experimental group comprising 13 subjects aged between 7 and 10 years old, with Class II malocclusion and anterior open bite, and a control group comprising 22 subjects similar in age, sex and mandibular plane angle. Maxillary/mandibular, horizontal/vertical, dental/skeletal movements (ANS, PNS, U1, U6, Co, Go, Pog, L1, L6) were assessed, based on 14 landmarks, 8 angles (S-N-ANS, SNA, PPA, S-N-Pog, SNB, MPA, PP/MPA, ANB) and 3 linear measures (N-Me, ANS-Me, S-Go).RESULTS:Treatment caused significantly greater angle decrease between the palatal and the mandibular plane of the experimental group, primarily due to an increase in the palatal plane angle. ANB, SNA and S-N-ANS angles significantly decreased more in patients from the experimental group. PNS was superiorly remodeled. Lower face height (ANS-Me) decreased in the experimental group and increased in the control group.CONCLUSIONS:The modified Thurow appliance controlled vertical and horizontal displacements of the maxilla, rotated the maxilla and improved open bite malocclusion, decreasing lower facial height.